A randomized controlled trial examining the impact of diversified nursing interventions on the circadian rhythm of sedated critically ill patients - Zhang, Mengfei; Shi, Aili; Xia, Chen; Du, Liping; Zheng, Shuangqin; Nan, Yong; Cheng, Zhen (Frontiers in Medicine, 2026)
Background:Circadian rhythms are cyclical processes within an organism that develop over time for the organism to better adapt to its environment. Disruption of the circadian rhythm by various factors can have both acute and chronic adverse effects on the health of the organism. Sedated patients in the intensive care unit often have severe circadian rhythm disturbances, in which care-related exogenous factors play an important role.MethodsIn this study, a randomized controlled trial design was adopted. Starting from the exogenous factors of nursing, the research objects that met the inclusion criteria were numbered. According to the inclusion order, they were odd numbered into the control group (receiving routine nursing care) and even numbered into the experimental group (receiving diversified nursing intervention). The two groups of research objects were divided into different sedation degree groups according to Richmond Agitation Sedation Scale (RASS) scores, which were divided into RASS 0–2 group, RASS -3–4 group and RASS -5 group, a total of six groups. The influence of diversified nursing intervention measures on patients’ circadian rhythm was evaluated by measuring the melatonin levels of the two groups.ResultsWe found that for patients with RASS scores of -3 to -4, diversified nursing interventions had a significant effect on melatonin concentrations in the 00:00–04:00 period (P < 0.05), indicating that diversified nursing interventions had a beneficial role in treating circadian rhythm disorders among sedated ICU patients.ConclusionThe circadian rhythm is crucial for critically ill patients and can be improved through diversified nursing interventions. This study provides relevant data for the future treatment of patients presenting with circadian rhythm disorders in the intensive care unit.